Body mass dynamics in hand reared clouded leopard (Neofelis nebulosa) cubs from birth to weaning. Issue 3 (25th February 2015) - Nájera, Fernando; Brown, Janine; Wildt, David E.; Virolle, Laurie; Kongprom, Urarikha; Revuelta, Luis; Goodrowe‐Beck, Karen
<x xml:space="preserve">Abstract</x> To study the dynamics of body mass changes in hand reared clouded leopards, we analyzed 3, 697 weight data points during the first 3 months of life in 49 cubs from 24 zoo‐born litters from 2003 through 2012. All cubs were fed the same formula mixture after a similar weaning protocol. The hand rearing process was divided into three periods based on feeding protocols: Stage 1: formula only (Days 1–28; Day 0 = day of birth); Stage 2, formula supplemented with protein (e.g., turkey baby food; Days 29–42); Stage 3, formula in decreasing amounts supplemented with meat (chicken and/or beef; Days 43–90). Weights at birth were 11.2% higher (P < 0.001) for males (n = 29) than females (n = 20). Daily weight gain was slowest (P < 0.05) during Stage 1 when cubs were fed straight formula only and fastest during Stage 3 when provided a mixture of formula and meat. Mean growth rate (± SD) during hand rearing differed (P < 0.05) by gender, being 34.6 ± 1.4 g/day for male and 30.0 ± 1.2 g/day for female cubs. Eighteen cubs (37%) exhibited mild to severe diarrhea during the study; however, palliative treatment resulted in similar (P > 0.05) growth and weaning weights compared to healthy counterparts. These are the first data documenting, on a large scale, the growth patterns for zoo born, hand reared clouded leopard cubs. Findings are valuable as an aid in managing this rare species, including for helping identify early onset of medical issues and further determining key factors regulating the first 3 months of development. Zoo Biol. 34:239–243, 2015. © 2015 Wiley Periodicals Inc.